2018
DOI: 10.1371/journal.ppat.1007033
|View full text |Cite
|
Sign up to set email alerts
|

Macrophage migration inhibitory factor is critical for dengue NS1-induced endothelial glycocalyx degradation and hyperpermeability

Abstract: Vascular leakage is one of the salient characteristics of severe dengue. Nonstructural protein 1 (NS1) of dengue virus (DENV) can stimulate endothelial cells to secrete endothelial hyperpermeability factor, macrophage migration inhibitory factor (MIF), and the glycocalyx degradation factor heparanase 1 (HPA-1). However, it is unclear whether MIF is directly involved in NS1-induced glycocalyx degradation. In this study, we observed that among NS1, MIF and glycocalyx degradation-related molecules, the HPA-1, met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
69
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(73 citation statements)
references
References 62 publications
3
69
0
1
Order By: Relevance
“…West Nile virus, which has high tropism to the brain, can induce MMP9 expression to facilitate viral entry into the brain [34]. MMP9 is also associated with endothelial glycocalyx degradation caused by dengue virus NS1 [43].…”
Section: Discussionmentioning
confidence: 99%
“…West Nile virus, which has high tropism to the brain, can induce MMP9 expression to facilitate viral entry into the brain [34]. MMP9 is also associated with endothelial glycocalyx degradation caused by dengue virus NS1 [43].…”
Section: Discussionmentioning
confidence: 99%
“…Dengue fever virus, a family of flavivirus, is known to damage the glycocalyx that leads to the increase of vascular permeability. Chen et al 42 demonstrated the Dengue virus stimulates endothelial cells to secrete glycocalyx degradation factor heparanase and modulate immune cells to secrete matrix metalloproteinase. It still remains to be clarified but similar mechanisms may also exist in COVID‐19.…”
Section: Endothelial Damagementioning
confidence: 99%
“…Compared to IgA, IgM is a large pentamer (molecular radius 120 A˚) that is only able to pass the glomerular filtration barrier through large defects and shunts, and therefore detecting IgM in urine may indicate dysfunction of the glomerular filtration barrier [12]. Recent studies have suggested that the mechanism of vascular leakage observed in severe dengue cases is due to the disruption of the endothelial glycocalyx layer (EGL) by dengue non-structural protein 1 (NS1) [28,29]. In fact, a clinical study by Suwarto et al, found that two of the four components of EGL were elevated in the serum of severe dengue patients [30].…”
Section: Final Case Classificationmentioning
confidence: 99%